MASALAH DALAM SISTEM PRE PROJECT SELLING APARTEMEN GRAND CUT MEUTIA - Nancy Glhoria Situmorang; Kartika Sari, Elsi; Situmorang, Nancy Glhoria (Faculty of Law, Universitas Trisakti, 2023)
The Pre Project Selling system is a method of selling apartments that is used before the building process is complete. The developer, the buyer, and the guarantor agency all profit from this system since it allows marketing to take place even before construction is started. The PPJB. 401/Pdt.G/2020/Pn.Bks, which claims that the developer has breached promises, is accurate. This is known as the Pre-Project Selling System, but in reality it leads to many violations. It is normative juridical research-which is based on secondary data, analytical descriptive with inductive conclusions-was conducted to address these issues. The findings of the investigation, the analysis, and the judgment, all in one ruling decision number 401/Pdt.G/2020/Pn.Bks by the judge has imposed a sanction in which the company Selaras Mitra Sejati states that the developer has correctly broken a promise as described in the order letter in Article 8 Paragraph G there that after which the purchase order was merged with the PPJB. the judge's decision stating that the developer broke promises, such as the UURS regarding sanctions in Article 110, the sanctions that must be fulfilled in this decision are appropriate because they did not submit the PPJB for Grand Cut Meutia Apartments.